Reliability of the EOS Imaging System for Assessment of the Spinal and Pelvic Alignment in the Sagittal Plane - Kim, Sang Bum; Heo, Youn Moo; Hwang, Cheol Mog; Kim, Tae Gyun; Hong, Jee Young; Won, You Gun; Ham, Chang Uk; Min, Young Ki; Yi, Jin Woong (Clinics in orthopedic surgery, 2018)
The sagittal alignment of the spine and pelvis is not only closely related to the overall posture of the body but also to the evaluation and treatment of spine disease. In the last few years, the EOS imaging system, a new low-dose radiation X-ray device, became available for sagittal alignment assessment. However, there has been little research on the reliability of EOS. The purpose of this study was to evaluate the intrarater and interrater reliability of EOS for the sagittal alignment assessment of the spine and pelvis. Records of 46 patients were selected from the EOS recording system between November 2016 and April 2017. The exclusion criteria were congenital spinal anomaly and deformity, and previous history of spine and pelvis operation. Sagittal parameters of the spine and pelvis were measured by three examiners three times each using both manual and EOS methods. Means comparison -test, Pearson bivariate correlation analysis, and reliability analysis by intraclass correlation coefficients (ICCs) for intrarater and interrater reliability were performed using R package "irr." We found excellent intrarater and interrater reliability of EOS measurements. For intrarater reliability, the ICC ranged from 0.898 to 0.982. For interrater reliability, the ICC ranged from 0.794 to 0.837. We used a paired -test to compare the values measured by manual and EOS methods: there was no statistically significant difference between the two methods. Correlation analysis also showed a statistically significant positive correlation. EOS showed excellent reliability for assessment of the sagittal alignment of the spine and pelvis.